Status and Trends in Patenting of R&D Results in the National Academy of Sciences of Ukraine - Kossko, T.G. (Science and Innovation, 2024)
Some aspects of patenting of the R&D results, in particular, the industrial property objects in the field of materials science, have been identified and analyzed. The achievements of the NASU institutes in the patenting of R&D results in materials science have been analyzed in a comparative manner. The patenting processes in Ukraine and in world countries have been described.